Adaptation and Psychometric Test of the Presentation of Online Self Scale (POSS) in Indonesia - Elza Dhea Salsabila; Nida Mukhlishotul 'Izzah (Psychological Journal: Science and Practice, 2026)
The development of social media has encouraged individuals to increasinglyactively build and manage their self-image online through online self-presentation . This study aimed to adapt and test the psychometriccharacteristics of the Indonesian version of the Presentation of Online SelfScale (POSS) for adolescents. A total of 100 participants participated. 100sample participants with the participant criteria being male, late adolescents,namely 15-25 years old, and active students at Islamic boarding schools.The analysis used included person fit and item fit analysis of the Raschmodel, item-total correlation, confirmatory factor analysis (CFA), andreliability testing. These results indicate that all items meet the eligibilitycriteria of the Rasch model, the four-factor structure has been confirmed, andthe model fit index is in the good category. The reliability value is in thereliable category. The reliability value of the instrument The online self-presentation scale in Indonesia is reliable, supported by CFA results thatindicate adequate model fit. These findings indicate that the Indonesianversion of the POSS scale has good psychometric qualities. However,compared to the original version, the reliability coefficient of the adaptedversion is lower, so further research is needed to evaluate the consistency ofthis scale. This scale is expected to serve as a basis for further research onthe psychological dynamics of individuals constructing identities online.